Model Penelitian Campuran (Mixed Method) (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The research model (Mix Method) is an approach that combines quantitative and qualitative methods in one study to obtain a more comprehensive understanding of a phenomenon. The purpose of this writing is to explain the nature of the mixed research model (mix method), the importance of the mixed research model (mix method) in research, the types of mixed research (mix method) in research, the steps of the mixed research model (mix method) in research and what are the advantages and disadvantages of the mixture (mix method) in research. In this writing, the author uses the library research method, the author collects data from reference sources from various literatures such as books, journal articles, research reports, and other literature sources in accordance with the topic of discussion. The results in this paper show that the mixed research model (mix method) provides flexibility in research design and increases the validity of the results.